2012
DOI: 10.1186/1475-2891-11-76
|View full text |Cite
|
Sign up to set email alerts
|

Steam-cooking rapidly destroys and reverses onion-induced antiplatelet activity

Abstract: BackgroundFoods in the diet that can aid in the prevention of diseases are of major interest. Onions are key ingredients in many cuisines around the world and moreover, onion demand has trended higher over the past three decades. An important pharmacological aspect of onion is the ability to inhibit platelet aggregation. Raw onions inhibit platelet aggregation; however, when onions are boiled or heated, antiplatelet activity may be abolished.MethodsOnion quarters were steamed for 0, 1, 3, 6, 10, and 15 min. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…al. (2012), steam cooking was shown to destroy the onion induced antiplatelet activity without changing the total polyphenolic concentration (Hansen et al, 2012), suggesting that the negative effects of heating triggered destruction of sulfur bioactive compounds. Additionally, the formation of allicin in fried garlic at 180 °C significantly decreased with processing (de Queiroz et al,…”
Section: Impact Of Temperature In Situmentioning
confidence: 98%
See 1 more Smart Citation
“…al. (2012), steam cooking was shown to destroy the onion induced antiplatelet activity without changing the total polyphenolic concentration (Hansen et al, 2012), suggesting that the negative effects of heating triggered destruction of sulfur bioactive compounds. Additionally, the formation of allicin in fried garlic at 180 °C significantly decreased with processing (de Queiroz et al,…”
Section: Impact Of Temperature In Situmentioning
confidence: 98%
“…chewing, crushing, etc.). This results in the formation of chemically unstable sulfinic acids which can subsequently be converted to a range of sulfurous based compounds, for example, thiosulfinates (TSs), which can undergo further dissociation and rearrangements to volatile and non-volatile compounds (Hansen et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…The main bioactive constituents in alliums include organosulfur compounds (OSCs) and polyphenols [10]. However, the complex chemistry of OSCs, due to their highly-volatile and thermally-unstable nature, likely impairs their health benefits [10][11][12][13]. In this context, allium polyphenols, with relatively higher stability than OSCs and associated antioxidant functions have emerged as more viable bioactive constituents in of Allium-derived polyphenols, in particular, flavonols, are attributed to their antioxidant activity which governs their functional properties including anti-inflammatory, antimicrobial, antiglycemic, and anticancer effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The main bioactive constituents in alliums include organosulfur compounds (OSCs) and polyphenols [ 10 ]. However, the complex chemistry of OSCs, due to their highly-volatile and thermally-unstable nature, likely impairs their health benefits [ 10 , 11 , 12 , 13 ]. In this context, allium polyphenols, with relatively higher stability than OSCs and associated antioxidant functions have emerged as more viable bioactive constituents in Allium species.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn poses a dilemma for consumers because increased pungency necessitates cooking to render onions and garlic palatable. Numerous studies have demonstrated that cooking and heating reduce or destroy in vitro health-related properties such as the ability of these vegetables to inhibit platelet aggregation (Chen et al, 2000;Hansen et al, 2012). Thus, significant attempts have been made to breed onion for lower amounts of pungency and associated organosulfur compounds so that the vegetables can be more palatable and desirable in raw form.…”
Section: Other Considerations: Marketing Plant Biology and Nutrigenmentioning
confidence: 99%